Study of the effect of zinc oxide on the antifungal action of the polymer blend (unsaturated polyester and natural rubber) for industrial applications - R. A. Nassif; A. M. Haleem; R. H. Hilal; A. A. Nsaif (Хімія, фізика та технологія поверхні)
Incorporating inorganic nanoparticles into polymers has produced polymer nanostructure materials with high-performance and multifunctional polymer features that exceed standard polymer composites. Polymer nanocomposites have multifunctional qualities, such as increased resistance to moisture and fungal and antibacterial properties. In this study, a polymeric blend of unsaturated polyester and natural rubber (80 / 20) was prepared as a control material, and it was then reinforced with zinc oxide nanoparticles (ZnONPs) with weight ratios (1, 1.5, 2, 2.5, and 3 %) in gradual addition with continuous stirring. The X-ray diffraction analyses and water diffusion coefficients were examined. The diffusion coefficient of the composite material with a concentration of 2 % had the highest value, after which the values began to fall, while the increase was linear at less than this concentration. The X-ray diagram revealed that the composite material with a concentration of 1 % had the lowest values of 2?, and that as the concentration increased, the values increased. Antimicrobial activity was conducted for two types of soil microbes, Fusarium solani and Streptomyces lividans, using the disc diffusion method, and inhibition of biofilm formation was observed at 72 hours of incubation time, with inhibition rates reaching 40.61 and 69.39 % in both Streptomyces lividans and Fusarium solani, respectively. It can also be noted the clear effect of zinc nanoparticles on the formation and visualization of biofilms in both organisms, as it was significantly affected by the treatment with an increase in concentration. Based on these findings, it appears that the synthetic blends that are reinforced with ZnONPs could be a promising material for water containers.